Adaptation of form and meaning in the poems of Amiri Firoozkoohi - Ali Taqavi (تاریخ ادبیات)
Adapting and recreating the meanings and themes of different texts has always been current among the creators of literary texts for centuries. Amiri Firoozkoohi in the field of contemporary poetry, is a traditionalist stylist poet with his own language and expression, who with his delicate and perspicacious talent and with his good knowledge and cognizance on Persian and Arabic language and literature, was able to create and express various meanings and themes of poetry in his poems. Nevertheless, he has been influenced by other texts in paying attention to the themes and meanings of poetry, and in most cases, he has included them in an artistic way in his poems. In the present article, by descriptive and analytical methods, the influence of different texts on Amiri’s poetical works has been reviewed and criticized. The research findings reveal, contrary to opinion of some researchers, Amiri is not simply influenced by Saeb Tabrizi. the poet is influenced by the Quran and hadiths in some of his themes, and in another part he has influenced by the poetic and prose literary texts of other Iranian and non-Iranian poets and writers, especially the poets of the fifth to eleventh centuries AH, Like Khaghani, Saadi, Molavi and Saeb.